2020
DOI: 10.1177/2043610620944927
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling the products of global flows: A model for a children’s global (un)makerspace

Abstract: This article discusses one specific form of makerspace for children – hereafter, referred to as (un)makerspace – whose activities consist mainly in dismantling discarded toys and electronics, characterised as a global makerspace. The article presents the activities of children participating in a number of makerspaces in Melbourne, Australia. The ‘materials’ children engaged with, mostly discarded toys and electronics, the detritus of global capitalist flows, became of prime importance and active agents in acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…These findings prompted further attempts to foster women's engagement and creative development in makerspaces by combining practical activities [56,98]. Velicu and Giannis showed that playing with support tools in makerspaces could dramatically change the way children perceive and approach a task demanding creative skills [83]. Applying design thinking in makerspaces was found to enhance open-ended, flexible, and transferable skills, such as creativity and critical thinking [46].…”
Section: Person-focused Studiesmentioning
confidence: 99%
“…These findings prompted further attempts to foster women's engagement and creative development in makerspaces by combining practical activities [56,98]. Velicu and Giannis showed that playing with support tools in makerspaces could dramatically change the way children perceive and approach a task demanding creative skills [83]. Applying design thinking in makerspaces was found to enhance open-ended, flexible, and transferable skills, such as creativity and critical thinking [46].…”
Section: Person-focused Studiesmentioning
confidence: 99%
“…These projects are of particular interest in the education of children which increases investment in technology, science, engineering, art and math (STEAM), and it is of great importance in preparing students for future society. In this way, the elements of digital manufacturing are part of school educational projects at early ages, as in the "Arcángel: D" project developed by the Arcángel Primary School with the collaboration of the FabLab Media Lab Prado [31] or MAkey Project with the aim of understanding the role of makerspaces in developing young children's digital literacy and creativity [32][33][34][35].…”
mentioning
confidence: 99%